2010
DOI: 10.1192/bjp.bp.109.065748
|View full text |Cite
|
Sign up to set email alerts
|

Economic evaluation of online computerised cognitive–behavioural therapy without support for depression in primary care: randomised trial

Abstract: Major depression is a common mental health problem in the general population 1 and is associated with substantial reductions in quality of life.2,3 Cost-of-illness studies reveal that the economic burden of depression is considerable. 4 However, many people with depression attending primary care do not receive the care they need. There is little evidence about the effectiveness of pharmacotherapy in patients with mild to moderate depression 5 and psychological treatments in primary care are scarce and costly. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
110
3
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(121 citation statements)
references
References 35 publications
3
110
3
3
Order By: Relevance
“…The comparison of computerized CBT and usual care showed a high probability of cost-effectiveness [39]. Differing results are presented by Gerhards et al [36]. They found that computerized CBT was less expensive and less effective in comparison to usual care.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…The comparison of computerized CBT and usual care showed a high probability of cost-effectiveness [39]. Differing results are presented by Gerhards et al [36]. They found that computerized CBT was less expensive and less effective in comparison to usual care.…”
Section: Resultsmentioning
confidence: 95%
“…Three studies were RCTs [36,37,38], while 1 was a modelling study [39]. Two studies employed a societal perspective [36,38], 1 study a third-party payer perspective [37] and for 1 study, the perspective was not determinable [39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Un ECC con tres brazos comparó un tratamiento computarizado de orientación cognitivo conductual administrado en línea llamado "Coloree su vida", el manejo usual de la depresión llevado a cabo por un médico general y ambos juntos no encontrándose diferencias signifi cativas a los seis meses entre estas tres posibilidades en relación a sintomatología depresiva y calidad de vida 15 ;sin embargo, los análisis costo efectividad favorecían al tratamiento cognitivo conductual solo 16 . Cinco ECC prueban el uso del teléfono en el tratamiento de la depresión.…”
Section: Depresiónunclassified